The Distributist Paradigm as Shown through Some Objections - Cross, Bryan R. (American catholic philosophical quarterly, 2025)
In this paper I argue that distributism should be understood as part of a paradigm composed of other moral principles, such that living in accord with distributism requires and presupposes the practice of these moral principles. To support my argument, I use a criticism of distributism by Alexander Salter in his recent book The Political Economy of Distributism: Property, Liberty, and the Common Good to illustrate the paradigmatic nature of the difference between the distributist paradigm and that of economic liberalism. I then consider some other objections to distributism from its contemporary critics, showing how these criticisms make use of assumptions within economic liberalism that are not shared by the distributist paradigm.